Establishment of a somatic embryogenesis protocol for in vitro olive plant propagation – a focus on the valorization of the Portuguese cv. 'Galega vulgar'. - Pires, Rita (2020)
Due to its capacity to regenerate plants from a single cell, in vitro somatic embryogenesis, apart from being an efficient plant propagation system is also fundamental to assist plant breeding by genetic transformation, and fundamental research for validation of data coming from different omics. The establishment of efficient protocols for plant regeneration through somatic embryogenesis must be taken as the first achievement on the successful regeneration of a transgenic plant. Focused on the validation of transcriptomic data, achieved in the frame of a running project (OLEAVALOR) and in the potential use of genetic engineering methodologies to further assist olive breeding programs, a research work has been carried out to establish an efficient somatic embryogenesis protocol for the Portuguese olive cv. 'Galega vulgar'. This cultivar is characterized by high quality olive oils and is still today the most representative of the traditional Portuguese olive orchards. However, it also presents several agronomic problems that highly limit its use in modern high density olive orchards, being mandatory the establishment of a breeding line for its valorisation. This study aimed on taking a first step in this direction, seeking to obtain an efficient somatic embryogenesis protocol that could later be used in breeding programs using genetic engineering approaches (e.g. cisgenesis, CRISPR/Cas9). Leaf petioles, taken from in vitro growing plantlets, as well as radicles and cotyledons, taken from mature seeds, were used as initial explants. The culture media composition and culture conditions were adapted from available reports (Rugini and Caricato 1995; Rugini and Silvestri 2016; Cerezo et al. 2011). A protocol for plant regeneration via somatic embryogenesis was achieved when mature zygotic embryos were used as initial explants. From the same initial explants, repetitive somatic embryogenesis was also successfully established, making available plant material for genetic transformation experiments. Regarding the use of leaf petioles from mature tissues, despite the formation of calli and the neoformation of leaf structures, it was not possible to obtain somatic embryos. Nevertheless, the results allow to foresee encouraging perspectives for further development of a protocol based on the use of adult plant material as initial explant.